A Fluorescence‐Based Assay to Monitor SUMOylation in Real‐Time. (7th July 2020) - Tripathi, Vasvi; Das, Ranabir
Abstract: The small ubiquitin‐like modifier (SUMO) is an important post‐translational modifier that regulates various cellular processes. Extensive investigations have been made to comprehend the enzymatic process and consequence of SUMOylation. In vitro SUMOylation assays are invaluable for understanding the fundamental mechanisms of SUMOylation. A majority of these assays monitor changes in the size of the substrate upon SUMO conjugation. Current methods typically detect the size difference through SDS‐PAGE and western blots, which makes these methods cumbersome, error‐prone, and time‐consuming. Here, we describe a fluorescence‐based assay for real‐time detection of SUMOylation. In the method, a fluorophore‐tagged substrate is used in the SUMOylation reaction. Upon SUMOylation, the size and correlation time (τc ) of the substrate increases, and so does its anisotropy. The rate of change in anisotropy with time reflects the efficiency of the SUMOylation machinery. The real‐time SUMOylation assay protocol is elegant, time‐saving, and less prone to errors. © 2020 Wiley Periodicals LLC. Basic Protocol : Fluorescent anisotropy‐based in vitro SUMOylation assay